The Relationship Between Leadership Functions and Performance Continuity in UAE Public Organizations: Moderating Role of Technology Business Analytics - Almheiri, Khalifa Mohamed Obaid; Romle, Abd Rahim; Omar, Rusdi (South Asian Journal of Social Sciences and Humanities, 2022)
Performance continuity is a major challenge for several organizations. In this regard the leadership plays a significant role. Thus, the purpose of the current research is to identify the role of leadership behaviors including challenging the process, inspiring a shared vision, and enabling others to act over performance continuity in UAE public sector organizations. Furthermore, the study also examined the moderating role of technology business analytics over the relationship between challenging the process, inspiring a shared vision, enabling others to act, and performance continuity in UAE public sector organizations. For the said purpose primary research has been conducted and the data has been collected from adopted instruments. The findings of the study revealed that challenging the process, inspiring a shared vision, and enabling others to act has a significant impact over performance continuity. Likewise the moderating role of technology business analytics over the relationship between challenging the process, inspiring a shared vision, enabling others to act, and performance continuity has also been found significant. The study enriched social exchange theory with the help of system theory to support the moderating role of technology business analytics. The study is significant for the academicians as well as practitioners to understand the leadership behavior required to enhance performance continuity.
Keywords: leadership; sustainability; performance continuity